Investor-state Dispute Settlement (ISDS) situation in Thailand - PHOTISARACH, SURAPEE (CRRU Law, Political Science and Social Science Journal, 2023)
International Investment Agreements (IIAs) were consists of well-recognized Bilateral Investment Treaties (BITs). BITS has less procedural need to prepare and also more specific than other IIAs. BITs were increasingly being used in the region of developing countries countries. BITs were bilateral agreements between state’s governments with commitment to promote increasing investment within their countries. Hence, BITs were legal mechanism to helped the committed countries to reached their goal of mutual benefit. BITs determined ISDS mechanism which was international investment dispute settlement under arbitration approach. The investor will be protected under government policy with mutual benefit between the them and the states. ISDS dispute resolution mechanism was arbitration which plague with issues such as long period of the process, inconsistent document translation and complicated arbitration procedure. States also found unable to control the cost of arbitration after the case was closed. Thereupon, the study of ISDS was established to increase its efficiency in encouraging international investment such as Thai-EU trade agreement in which EU suggest the establishment of international bilateral-investment court in place of arbitration.